The Relation Between Psychological Capital and Job Hopping with Job Satisfaction as a Mediator among Generation Z Employees - Puti, Kezia; P. Dwi Riyanti, Benedicta (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
This study aims to examine the relation between psychological capital and job hopping, with job satisfaction as a mediator among Generation Z employees. As a generation new to the workforce, Generation Z exhibits a high tendency to switch jobs, with turnover rates reaching up to 20%. While job hopping can provide diverse work experiences, expanded networks, and higher wages, it is often perceived by employers as a sign of low loyalty and commitment. Additionally, frequent job changes can be costly for organizations in terms of time, effort, and financial resources. This quantitative study involved 183 respondents aged 23-27 who had been employed at their current company for 1-2 years. The research utilized the Psychological Capital Questionnaire (PCQ), Minnesota Satisfaction Questionnaire (MSQ), and Job Hopping Intention Scale (JHI). Data were analyzed using path analysis with JASP. The results showed that psychological capital had a significant indirect effect on job hopping through job satisfaction. Specifically, higher psychological capital enhances job satisfaction, which in turn reduces the likelihood of job hopping. Future research could focus on specific industries or organizations, employ a job satisfaction instrument more tailored to Generation Z, and include a criterion for participants who have switched jobs within the past one to two years. The practical implication of this study is that organizations should develop initiatives that enhance employees' psychological capital, because these factors have a positive influence on job satisfaction and reduce turnover.